PENGEMBANGAN MODEL PEMBIMBINGAN UNTUK MENINGKATKAN KEMAMPUAN GURU DALAM MELAKUKAN REFLEKSI PEMBELAJARAN: Suatu Studi pada Program S1 PGSD Universitas Terbuka. - Julaeha, Siti (2010)
Teaching reflection can improve teachers' professional abilities. In order to undertake reflective practice that is beyond the present level of their abilities, expert's helps and professional support are needed by teachers. This study was designed to find out "a supervisory meeting model that is appropriate for facilitating teachers to enhance their ability in teaching reflection". Accordingly, the research objectives are to develop and validate a supervisory meeting model that can improve teachers' ability in conducting teaching reflection. An approach used in this study was a research and development approach consisting the preliminary study through a survey and a literature study, the model development through an action research and an evaluation at limited and broader field testing, and the validation testing through a quasi-experiment. This study was taken place at The S1 PGSD Program at the Indonesian Open Learning University and the research subject was student-teachers who took the Professional Capability Development (PCD/PKP) course and PKP supervisors at the Bandung regional center. Data collection techniques used in the study were document studies, desk evaluation, questionnaires, interviews, observations, and assignments of making reflective writings. Those data were analyzed by quantitative (mean, percentage, and non-parametric statistics: Wilcoxon Signed Rank Test and Mann-Whitney U-Test) as well as qualitative descriptive techniques. Research findings showed that the Model of Supervisory Meeting for Teaching Reflection that was developed based on a social constructivist theory and embedded with the idea of communities of practice and a clinical supervision approach was proved to be effective for increasing reflective writings scores of student-teachers of S1 PGSD Program. The Model of Supervisory Meeting for Teaching Reflection was applied through orientation, exploration, interpretation, and re-design activities with emphasizing on modeling, sharing, guided- and self-directed practicing, as well as taking continuous exercise writing reflective journals. The Model of Supervisory Meeting for Teaching Reflection can be an alternative model in fostering teachers' ability in conducting teaching reflection. In order to effectively implement this model, the S1 PGSD Program should develop manuals, video program, and online tutorial, as well as provide socialization of, training in, and monitoring the implementation of model in tutorial process. In addition, the findings of this study pose questions which demand further study.